Rancang Bangun Sistem Deteksi Kebakaran Gedung di Universitas Islam Lamongan Berbasis Mikrokontroller Menggunakan Radio Frekuensi - Affan Bachri (Universitas Islam Lamongan, 2019)
The process of firing is always unpredictable and predicted in advance. When it comes, what causes it, the level of coverage and how much impact it causes, are things that cannot be predicted by human capabilities. The design of a fire safety system that aims to improve the safety and comfort of occupants in the building. The analysis carried out is to measure and record temperature and conduct a series of several experiments. Temperature is equipped with Celsius (C) units and smoke uses PPM units (parts per million). By working, the smoke sensor and temperature will detect itself and work properly. And this is to avoid any errors caused by rising temperatures due to sunlight or smoke from cigarettes. If the LM35 temperature sensor reaches 40 C then the temperature will detect and the buzzer will sound the LED will be wrong and the LCD 2x16 will display